Towards Integrating Six Sigma Approach: Service Level Agreement Measurement and Monitoring (A Malaysian It Outsourcing Case Study) - et.al, Whee Yen Wong (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Service Level Agreements (SLAs) are critical for outsourcing and technological related vendors companies. SLAsare the key requirements for outsourcing implementation and deployment as well as are the key differentiator in the service provider’s offerings industry. Over time, SLAs drive behaviors delivering a minimum level of service to the provider resultant in limited room in innovation and improvement in SLA arrangement and SLA contract renewal. As such, outsourcing companies may deem become a commodity, lacking strategic, innovative and value-added partner to the business. In long run, outsourcing companies face challenges with rapidly changing business requirements that drives business agility to stay competitive. The paper attempts to investigate a vendor IT Service Company accountable for continuous measurement and reporting of SLA activities where agreed-on service levels face challenges. This paper aims to evaluate the practical applicability of Six Sigma approach (i.e. DMAIC (Define, Measure, Analyze, Improve and Control)) as a result of root-cause-analysis; where everyone working on the problem(s) stays focus, drive towards a root cause analysis and eventually address the problem directly. The result of this case study revealed how Six Sigma approach has successfully improve the SLA achievements by identifying the significant factors contributing remedies or penalties towards SLA measurements.